Innovative approaches in nursing education: Enhancing learning efficiency and critical thinking based on cooperative and project-based learning - Qiuxia, Xie; Jantharajit, Nirat; Srikhao, Sarit (Asian Journal of Contemporary Education, 2024)
The study investigates the impact of a blended teaching approach combining Cooperative and Project-Based Learning (CPBL) on the critical thinking abilities and learning efficiency of vocational nursing students, aiming to determine its effectiveness compared to traditional teaching methods. The study employed an experimental design, involving vocational nursing students divided into experimental and control groups. The experimental group participated in 20 instructional sessions using the CPBL approach, while the control group received traditional teaching. Learning outcomes were assessed through pre-test and post-test evaluations using the Learning Efficiency Assessment Scale (LEAS) and the Critical Thinking Ability Assessment Scale (CTAAS). The experimental group demonstrated significant improvements in learning efficiency (M=76.04, t=-10, p<0.05) and critical thinking skills (M=137.6, t=-4.33, p<0.05), while the control group showed only slight increases in learning efficiency (M=75.52, t=-2.316, p<0.05) and critical thinking (M=136.48, t=-2.113, p<0.05). These results affirm the superior effectiveness of the CPBL approach in fostering critical cognitive and psychomotor skills. This pedagogical strategy offers a robust framework for curriculum designers aiming to improve student performance and engagement in professional education settings.